RECONSTRUCTION OF LAW ON THE RETURN OF ASSETS TO VICTIMS OF INVESTMENT FRAUD IN MONEY LAUNDERING OFFENSES BASED ON THE PRINCIPLE OF JUSTICE - Erdiansyah; M. Musa; Thamrin S; Abd Thalib (International Conference On Law And Social Sciences, 2024)
The victim of investment fraud in a money laundering crime cannot reclaim their assets through criminal justice mechanisms because, in practice, utilizing criminal legal avenues would result in the state seizing those assets. To analyze this matter, a study will be conducted on two issues: Firstly, What is the urgency of reconstructing the law regarding the return of assets to victims of investment fraud in the context of money laundering offenses? And secondly, What is the ideal concept for regulating the return of assets to victims of investment fraud in money laundering laws based on principles of justice. The study on these two issues will employ the normative legal research method. The legal sources utilized consist of primary, secondary, and tertiary legal materials, employing the legislative approach method. Data analysis is conducted using qualitative descriptive data analysis by outlining relevant aspects of the study and subsequently drawing conclusions. The first conclusion emphasizes the urgency of enacting legal reconstruction concerning the restitution of assets for victims of investment fraud in the context of money laundering crimes. This urgency stems from the absence of explicit provisions in the Republic of Indonesia Law Number 8 of 2010 on the Prevention and Eradication of Money Laundering regarding this matter. Consequently, judicial decisions to confiscate the proceeds of crime to the state are deemed inappropriate, as they may lead to legal complications in the future. Such judicial rulings disregard both the principles of justice and legal certainty for victims of investment fraud. The two ideal concepts necessitate the regulation of asset return for victims of investment fraud within anti-money laundering laws explicitly to serve as a judicial foundation in decision-making. This is to ensure justice in the restitution of assets for victims of investment fraud.